Travels, Politics and Paul in the New Testament - Punt, J. (Scriptura, 2025)
This contribution on biblical travels focuses on the NT and Paul in particular, both regarding the significance of travel as a physical movement of people but also in terms of the related politics. Related to ancient and Jewish contexts, the NT’s travel discourses unfold in relation to issues of identity, to socialisation and as displacement discourse within the Roman imperial context. In this regard, travels were co-constituted by maps and borders, then as much as today. NT travels and travel discourse had significant political implications for the past and continue to be invoked in modern, analogical discourses like migration.